The effects of registration and delivery in the transactions of immovables in Chinese Civil Law - Jiayuan, Deng (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
According to Civil Code of China, the ownership of immovable is transferred through registration after the sales contract was signed. The delivery of immovable does not have the effect of transferring the ownership of immovable. The buyer has no real right to the immovable before registration after delivery of the immovable, and his right is limited to the creditor’s rights on the seller based on the sales contract. After the delivery, the possession, use and enjoy of such an immovable by the buyer are based on the creditor´s rights to the seller derived from the sales contract. In judicial practices, however, there are circumstances in which this general doctrine cannot be fully adhered to. This has often been a source of controversy among scholars.
Keywords: registration; delivery; transactions of immovables; Chinese Civil Law